Sistem Pendukung Keputusan Pemilihan Pegawai Honorer Terbaik Menggunakan Metode Visekriterijumsko Kompromisno Rangiranje - Fuad Surya Mawinar; Rakhmat Dedi Gunawan; Adhie Thyo Priandika (Journal of Data Science and Information Systems, 2023)
The problem that occurs is that there is no decision support system method to determine the selection of the best honorary employees in the Lampung Provincial Cooperative and MSME Office. The decision support system for selecting the best honorary employees uses the VIKOR method (visekriterijumsko kompromisno rangiranje) case study of the Cooperatives and MSMEs Office of Lampung Province. Design of decision support system for selecting the best honorary employees using the VIKOR method (visekriterijumsko kompromisno rangiranje) case study of the Cooperatives and MSMEs Office of Lampung Province using extreme programming methods which have stages, namely planning, design, coding, and testing. The ranking results use the VIKOR method in the decision support system for the Best Honorary Employee, the VIKOR method recommends Honorary Employee 5 as a candidate for Honorary Employee 5 with a VIKOR index value of 0.045 and get a rank of 1.